Hydrogen sulfide plays an important role by regulating endoplasmic reticulum stress in myocardial diseases - Zhao, Huijie; Fu, Xiaodi; Zhang, Yanting; Yang, Yihan; Wang, Honggang (Frontiers in Pharmacology, 2023)
Endoplasmic reticulum (ER) is an important organelle for protein translation, folding and translocation as well as the post-translational modification and the assembly of newly synthesized secreted proteins. When the excessive accumulation of misfolded and/or unfolded proteins exceeds the processing capacity of ER, ER stress is triggered. The integrated intracellular signal cascade, namely the unfolded protein response, is induced to avoid ER stress. ER stress is involved in many pathological and physiological processes including myocardial diseases. For a long time, hydrogen sulfide (H2S) has been considered as a toxic gas wiht rotten eggs. However, more and more evidences show that H2S is an important gas signal molecule after nitric oxide and carbon monoxide and regulate a variety of physiological and pathological processes in mammals. In recent years, the increasing studies have focused on the regulatory effects of H2S on ER stress in myocardial diseases, however, the mechanism is not very clear. Therefore, this review reviewed the role of H2S regulation of ER stress in myocardial diseases and deeply analyzed the relevant mechanisms so as to laid the foundation for the future researches.